Drone-assisted herbicide optimization for energy efficiency, weed control and economics in transplanted rice (Oryza sativa) - JEEVAN, NARAYANASWAMY; PAZHANIVELAN, SELLAPERUMAL; KUMARAPERUMAL, RAMALINGAM; SIVAMURUGAN, A P; KANCHETI, MRUNALINI (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during summer and rainy (kharif) seasons of 2021 and 2022 at Agricultural Research Station (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Bhavanisagar, Tamil Nadu to evaluate the efficiency, economics and energetics of drone-based herbicide spray (fluid) application in transplanted rice (Oryza sativa L.). During the experiment the application of pre-emergence and post-emergence herbicides was done using drone and knapsack sprayer to assess the weed control efficiency (WCE). Treatments included 3 herbicide combinations, viz. pyrazosulfuron ethyl as pre-emergence (PE); pyrazosulfuron ethyl as pre-emergence (PE) fb bispyribac sodium as PoE; and pyrazosulfuron ethyl as PE fb metsulfuron methyl + chlorimuron ethyl as PoE; and 4 spray fluids applied using drone and knapsack sprayer (25, 37.5, 75 and 500 litre/ha). Weed free and unweeded check plot were used as reference for calculating WCE. Application of pyrazosulfuron ethyl fb bispyribac sodium using knapsack sprayer reduced weed density from 77.74–86.45% and weed dry weight from 89.60–91.40% over unweeded plot. Moreover, it was found on par with drone application of 37.5 litre/ha using herbicides during both the seasons. Interaction effect between herbicides and drone spray fluids was found to be non-significant. Pyrazosulfuron ethyl fb bispyribac sodium application through knapsack sprayer (500 litre/ha) and drone (37.5 litre/ha) produced higher grain yield and straw yield. Higher net return, benefit: cost ratio (2.49 and 2.40), energy-use efficiency (13.44 and 13.40 MJ) and energy productivity (0.414 and 0.416 kg/MJ) were noticed with drone application of pyrazosulfuron ethyl fb bispyribac sodium using 37.5 litre/ha spray fluid in both the seasons. From the experiment, drone application of pyrazosulfuron ethyl fb bispyribac sodium with spray volume of 37.5 litre/ha was found as an effective strategy to manage weeds in transplanted rice and more advantageous in terms of energy-use efficiency and profitability.